PERAN REKRUTMEN DAN SELEKSI DALAM MENINGKATKAN KINERJA KARYAWAN: STUDI TINJAUAN PUSTAKA - Hadiati, Eti; Junaidah; Nurjanah, Siti; Salsabilla, Naila Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Recruitment and selection processes play a crucial role in determining the quality and performance of employees within organizations. This study investigates the impact of recruitment and selection on employee performance, particularly in relation to job placement in various organizations. A literature review methodology was employed to examine recent research on how effective recruitment and selection strategies influence organizational outcomes, employee satisfaction, and job performance. Findings from various studies suggest that competency-based recruitment and selection lead to higher employee performance and productivity. Additionally, transparent and fair selection processes improve employee engagement, motivation, and retention. The role of technology in recruitment and selection has also been highlighted as a key factor in enhancing efficiency and reducing biases in the selection process. However, despite the advantages of technological tools, human judgment remains critical in evaluating candidates’ fit with organizational culture and job requirements. This study concludes that recruitment and selection processes, when conducted effectively, significantly contribute to enhancing employee performance and organizational success.